'EDUCATING A GIRL MEANS EDUCATING A WHOLE NATION' GENDER MAINSTREAMING, DEVELOPMENT AND ISLAMIC RESURGENCE IN NORTH CAMEROON†. (14th October 2013) - van, José C. M.; van, Anouka; Davids, Tine
<x xml:space="preserve">Abstract</x> Abstract: The paper is an example of 'local' reception of global terminology concerning gender in the Cameroonian context: a gender awareness training for local religious, Muslim, and political leaders is analyzed. These leaders want development that departs from Islamic 'roots', emphasizing the importance of women's education. However, a concept such as 'gender' turned out to be incongruent with local concepts for relations between human beings. Because of that, they needed not reflect on their own attitudes as male citizens. Their implicit view is, so was discovered after analysis of the workshop, that a process of Islamization would automatically lead to gender mainstreaming. Copyright © 2013 John Wiley & Sons, Ltd.